2004
DOI: 10.1073/pnas.0401413101
|View full text |Cite|
|
Sign up to set email alerts
|

Unique domain anchoring of Src to synaptic NMDA receptors via the mitochondrial protein NADH dehydrogenase subunit 2

Abstract: Src is the prototypic protein tyrosine kinase and is critical for controlling diverse cellular functions. Regions in Src define structural and functional domains conserved in many cell signaling proteins. Src also contains a region of low sequence conservation termed the unique domain, the function of which has until now remained enigmatic. Here, we show that the unique domain of Src is a protein–protein interaction region and we identify NADH dehydrogenase subunit 2 (ND2) as a Src unique domain-interacting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
119
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 50 publications
(51 reference statements)
5
119
0
Order By: Relevance
“…SFKs can be modulated by tyrosine phosphatases, G-protein-coupled receptors, receptor protein tyrosine kinase signaling, the Ras pathway, and the cytokine receptor and integrin pathways. Many of the physiological actions of NMDA receptors are critically dependent upon SFKs (Gingrich et al, 2004;Hayashi and Huganir, 2004;Kalia and Salter, 2003;Lu et al, 1999). As an example, SFKs are necessary for the induction of long-term potentiation in the CA1 region of hippocampus (Salter and Kalia, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…SFKs can be modulated by tyrosine phosphatases, G-protein-coupled receptors, receptor protein tyrosine kinase signaling, the Ras pathway, and the cytokine receptor and integrin pathways. Many of the physiological actions of NMDA receptors are critically dependent upon SFKs (Gingrich et al, 2004;Hayashi and Huganir, 2004;Kalia and Salter, 2003;Lu et al, 1999). As an example, SFKs are necessary for the induction of long-term potentiation in the CA1 region of hippocampus (Salter and Kalia, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop a practical reagent to disrupt anchoring of Src in the NMDAR complex in vivo, we synthesized a series of overlapping 10-amino acid peptides covering Src40-58, the region in the unique domain we had previously identified in vitro as crucial for the Src-ND2 interaction 18 . We found that a peptide consisting of amino acids 40-49 of Src, Src40-49, but not Src45-54 or Src49-58, bound to ND2.1, the interacting region of ND2 (Fig.…”
Section: Constructing a Src-nmdar Uncoupling Peptide For Use In Vivomentioning
confidence: 99%
“…Within the NMDAR complex, the non-receptor tyrosine kinase Src is a critical regulatory hub through which multiple intracellular signaling cascades converge to increase NMDAR activity 16 . Src is anchored within the NMDAR complex through an adaptor protein which we have identified as NADH dehydrogenase subunit 2 (ND2) 18 . Blocking the interaction between the Src unique domain and ND2 releases Src from the NMDAR complex, separating the enzyme and substrate, thereby inhibiting Src-mediated upregulation of NMDAR activity 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a mitochondrial DNA (mtDNA) encoded protein, ND2, actually serves to anchor NMDA receptor complexes to a regulatory tyrosine kinase [6]. Thus, in addition to playing an essential role in excitotoxic cascades, mitochondria and NMDA receptor complexes structurally overlap.…”
Section: Introductionmentioning
confidence: 99%